2017
DOI: 10.1016/j.ijcard.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Does pre-existing aortic regurgitation protect from death in patients who develop paravalvular leak after TAVI?

Abstract: In patients with severe AS treated with balloon-expandable TAVI, the presence of PVL, but not pre-procedural AR, was a major predictor of adverse outcome. Preoperative LV dilatation seemed to offer some clinical advantages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The impact of PVL and PPM on clinical outcome and LV recovery after TAVR is still a matter of debate, and the scientific evidence on this field are controversial. Previous reports suggested that mild PVL is commonly observed after TAVR and usually leads to a benign outcome (36). However, a meta-analysis of 45 studies including around 13,000 patients concluded that moderate or greater post-TAVR PVL was associated with a more than 2-fold increase in overall all-cause mortality (37).…”
Section: Discussionmentioning
confidence: 99%
“…The impact of PVL and PPM on clinical outcome and LV recovery after TAVR is still a matter of debate, and the scientific evidence on this field are controversial. Previous reports suggested that mild PVL is commonly observed after TAVR and usually leads to a benign outcome (36). However, a meta-analysis of 45 studies including around 13,000 patients concluded that moderate or greater post-TAVR PVL was associated with a more than 2-fold increase in overall all-cause mortality (37).…”
Section: Discussionmentioning
confidence: 99%
“…PVL has shown to be correlated to increased mortality at 1 year (19,20), especially in patients with preoperative valve stenosis and no regurgitation (with no previous ventricular dilation) (21). For this reason, when it comes to treating intermediate and low risk patients, the occurrence of "more than mild" PVL should unquestionably be avoided.…”
Section: Hemodynamic Performancementioning
confidence: 99%
“…Many pivotal TAVR clinical trials have excluded patients with severe AR and reports on outcomes in the MAVD population are limited [ 8 10 ]. The data available is inconclusive in that some studies have shown improved survival among MAVD patients after TAVR [ 11 13 ], while others have not [ 14 16 ]. We performed a meta-analysis to compare the 1-year mortality outcomes of TAVR among patients with MAVD and AS.…”
Section: Introductionmentioning
confidence: 99%